Pengaruh Kual Pengaruh Kualitas Produk, Kualitas Pelayanan dan Word Of Mouth terhadap Keputusan Pembelian: Survei Pada Konsumen DNA SPOT CAFÉ Surakarta - Vera Dewinta Wulandari; Marjam Desma Rahadhini (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study examines the influence of product quality, service quality, and word of mouth on purchase decisions at DNA Spot Café Surakarta, based on 100 randomly selected respondents. Multiple linear regression analysis shows that service quality and word of mouth have a positive and significant effect, while product quality is not significant. The coefficient of determination of 61.3% indicates that the independent variables explain most of the variation in purchase decisions, contributing to marketing management research in the café industry. The results highlight the crucial role of service quality in shaping customer perceptions and driving decision-making in the café industry. High-quality service fosters positive customer experiences, which, in turn, encourage repeat visits and enhance loyalty. Additionally, the significant influence of word of mouth underscores the importance of social interactions and customer recommendations in the decision-making process, especially in a service-based business like a café, where personal experiences are often shared and valued among peer groups. Conversely, the insignificance of product quality suggests that while product standards are important, they may not be the primary driver of purchase decisions at DNA Spot Café. This indicates that customers may prioritize the overall experience, atmosphere, and peer recommendations over product differentiation when choosing where to dine or spend leisure time. These findings contribute to the body of marketing management research, particularly in the context of the café industry, by emphasizing the strategic importance of service excellence and customer engagement strategies to enhance brand reputation and influence consumer behavior. Future research could explore additional factors such as pricing, promotional strategies, and customer loyalty programs to provide a more comprehensive understanding of purchase decision dynamics.